Wild Mushrooms - Mohamad Hasnul, Bolhassan; Rahah, Mohd Yakup; Heira Vanessa, Nelson (UNIMAS Publisher, 2024)
Mushrooms are recognized for their ecological significance. The Baleh region of Sarawak, Malaysia, is a pristine and known biodiversity- Lrich area on Borneo, yet, its mushrooms had awaited exploration and study. 'Wood-decay' mushrooms are essential in decomposing woody debris derived from trees and other woody plants, representing most of the vegetation in forest ecosystems. Mushrooms of the Baleh region can be classified across four taxonomic orders. Nine families and 12 genera have been identified and recorded. Notably, the order Polyporales showed the highest number of species. Within the order Polyporales, the family Polyporaceae was the most dominant, with four species: Microporus affinis, Microporus xanthopus, Favolus emerici and Trametes sanguinea. Ganoderma sp. and Microporus sp. were frequently encountered. Wood-inhabiting mushrooms are an essential part of the forest ecosystem and play an important role in wood degradation.